Browsing by an invasive herbivore promotes development of plant and soil communities during primary succession. (25th July 2016) - Bellingham, Peter J.; Kardol, Paul; Bonner, Karen I.; Buxton, Rowan P.; Morse, Chris W.; Wardle, David A.
Summary: Invasive herbivores can strongly affect ecosystems by reducing or removing native plant species, and early in primary successions they could have enduring consequences for plant community assembly and ecosystem functioning, although this has seldom been explored. Invasive brushtail possums ( Trichosurus vulpecula ) browse from ground levels to forest canopies in New Zealand, including on plant species common early in primary succession. We used exclosures (fenced on the top as well as the sides) and corresponding control plots to study effects of brushtail possums on primary successions on bare landslide surfaces in the South Island of New Zealand. We then conducted repeated measurements of the plant community over 11 years and at the end also quantified soil abiotic and biotic properties. Above‐ground, plant biomass increased from close to zero to > 1000 g dry mass m −2 after 11 years in both exclosures and control plots, with significantly more biomass of the N2 ‐fixing tree Carmichaelia odorata in the controls. Brushtail possums reduced the biomass in the control plots of small‐stature grasses and sedges in the first 3 years. Plant species richness was greater in control than exclosure plots throughout the experiment. Below‐ground, soil carbon and nitrogen concentrations and the biomass of all major soil microbial groups were significantly greater in the control than exclosure plots, although soil nematode abundances were not. Below‐ground effects could be attributed to the greater biomass of Carmichaelia in control plots. Synthesis . Our study shows that an invasive herbivore exerted strong effects on the rate and trajectory of primary succession by altering plant community assembly. Herbivore exclusion resulted in reduced biomass of a key N2 ‐fixing tree that drives forest development, with important below‐ground consequences. These results support a view that restoration of ecosystems needs to consider the consequences of altering plant community structure before removing invasive herbivores. Abstract : This study used replicated fenced exclosures (including roofs), paired with controls, to determine the effects of an arboreal introduced herbivore (brushtail possum) on plant and soil communities over 11 years during primary successions on landslides. Surprisingly, the rate of succession towards rain forests, above‐ and below‐ground, was more rapid in the controls to which possums had access. This was because biomass of a key nitrogen‐fixing tree was reduced when possums were excluded. The study underscores the need to consider the consequences of altering plant community structure before removing invasive herbivores, with the aim of restoring ecosystems.